2018
DOI: 10.1002/jcb.27342
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DGCR5 represses hepatocellular carcinoma progression by inactivating Wnt signaling pathway

Abstract: Increasing studies have indicated that long noncoding RNAs (lncRNAs) exert important roles in hepatocellular carcinoma (HCC). Therefore, it is of great significance to identify the dysregulated lncRNAs in HCC. According to the previous reports, it has been suggested that DiGeorge syndrome critical region gene 5 (DGCR5) might participate in HCC and can serve as potential biomarker for HCC. In our current study, we concentrated on the biological function and roles of lncRNA‐DGCR5 in HCC. It was indicated that DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Moreover, a recent study revealed that the upregulation of DGCR5 was indicator for better outcome of bladder cancer and interacted with AT‐rich interaction domain 1A to regulate cancer cell progression . In addition, DGCR5 was demonstrated to inhibit the development of hepatocellular carcinoma through targeting the Wnt signaling pathway . Importantly, DGCR5 was also revealed to have tumor suppressive role in lung cancer…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study revealed that the upregulation of DGCR5 was indicator for better outcome of bladder cancer and interacted with AT‐rich interaction domain 1A to regulate cancer cell progression . In addition, DGCR5 was demonstrated to inhibit the development of hepatocellular carcinoma through targeting the Wnt signaling pathway . Importantly, DGCR5 was also revealed to have tumor suppressive role in lung cancer…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, DGCR5 was demonstrated to inhibit the development of hepatocellular carcinoma through targeting the Wnt signaling pathway. 9 Importantly, DGCR5 was also revealed to have tumor suppressive role in lung cancer. 10 Previously, we showed increased miR-211 expression in NSCLC, however, we did not explore the upstream molecule that can target miR-211 at that time.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have identified numerous lncRNAs associated with HCC, such as DGCR5 and lncRNA PCAT-1. These lncRNAs contribute to the regulation of the proliferation, migration and invasion of HCC cells [18][19]. Our previous study showed that LINC00355:8 expression is increased in HCC compared with normal liver tissue; however, the biological function of LINC00355:8 in HCC remains unknown [11].…”
Section: Discussionmentioning
confidence: 99%
“…20 Increasing evidence has revealed that DGCR5 is a suppressor of lung cancer, cervical cancer, gastric cancer and hepatocellular carcinoma progression. [21][22][23][24] Moreover, down-regulation of DGCR5 correlates with poor prognosis in hepatocellular carcinoma and bladder cancer. 25,26 A recent study reported that DGCR5 inhibited the proliferation, aggressiveness phenotypes, and EMT of glioblastoma cell.…”
Section: Introductionmentioning
confidence: 99%